Thiolated Alginate-Poly(Lactic-Co-Glycolic Acid) Aptamer-Functionalised As A Tamoxifen-Curcumin Nanocarrier Against Resistant Breast Cancer Cell - Chiu, Hock Ing (2023)
The objective of this project is to create thiolated alginate nanoparticles with the surface fabrication of poly(lactic-co-glycolic acid) (PLGA) and AS1411 aptamer for targeted delivery of tamoxifen (TAM) and curcumin (CUR) to resistant breast cancer cells.